2019
DOI: 10.1007/s10840-019-00617-9
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic features, mapping and ablation of idiopathic outflow tract ventricular arrhythmias

Abstract: Purpose Idiopathic outflow tract ventricular arrhythmias are ventricular tachycardias or premature ventricular contractions presumably not related to myocardial scar or disorders of ion channels. These arrhythmias have focal origin and display characteristic electrocardiographic features. The purpose of this article is to review the state of the art of diagnosis and treatment of idiopathic outflow tract ventricular arrhythmias. Methods We systematically reviewed scientific literature about idiopathic outflow t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 55 publications
1
22
0
2
Order By: Relevance
“…During IVAs haemodynamic impairment or serious symptoms are unusual, but patients can have palpitations, atypical chest pain or LV dysfunction. IVAs are distinguished by whether or not they originate from the outflow tracts and display specific electrocardiographic features [29].…”
Section: Clinical Presentation and Electrocardiographic Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…During IVAs haemodynamic impairment or serious symptoms are unusual, but patients can have palpitations, atypical chest pain or LV dysfunction. IVAs are distinguished by whether or not they originate from the outflow tracts and display specific electrocardiographic features [29].…”
Section: Clinical Presentation and Electrocardiographic Morphologymentioning
confidence: 99%
“…The origins of RVOT and LVOT can be distinguished on the ECG by the precordial R-wave transition from a predominate S wave to a predominate R wave (rS to Rs). Transitions before V3 indicate an LVOT source and after V3 indicate an RVOT source [29][30][31][32], as seen in Figure 1. When LBBB QRS morphology is observed and the precordial transition occurs at V3, comparison to the patient's sinus rhythm precordial transition can be useful: a V2 transition ratio ≥ 0.60 suggests LVOT origin with high sensitivity and specificity [33,34].…”
Section: Clinical Presentation and Electrocardiographic Morphologymentioning
confidence: 99%
“…Additionally, review of the patient's CT chest revealed osseous involvement of the sternum and of the left aspect of the mediastinum, causing extrinsic compression of the RVOT, with elevated right heart pressures seen on echocardiography. The RVOT is a known arrhythmogenic source of many ventricular arrhythmias, such as premature ventricular contractions, ventricular bigeminy, and sustained ventricular tachyarrhythmias, 5,6 and a site of involvement identified in early case reports with extrinsic compression from anterior chest involvement from lymphoma and new diagnosis of ventricular arrhythmia. 7,8 In patients with advanced tumor burden and either extrinsic or intrinsic cardiac involvement, there are no current consensus guidelines for selecting an ideal candidate for transcatheter or minimally invasive management, though it seems a reasonable consideration for patients who may receive a direct palliative benefit from intervention, or in those with a stable tumor burden and related cardiovascular symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, review of the patient’s CT chest revealed osseous involvement of the sternum and of the left aspect of the mediastinum, causing extrinsic compression of the RVOT, with elevated right heart pressures seen on echocardiography. The RVOT is a known arrhythmogenic source of many ventricular arrhythmias, such as premature ventricular contractions, ventricular bigeminy, and sustained ventricular tachyarrhythmias, 5,6 and a site of involvement identified in early case reports with extrinsic compression from anterior chest involvement from lymphoma and new diagnosis of ventricular arrhythmia. 7,8…”
Section: Discussionmentioning
confidence: 99%
“…From the clinical point of view, the myocardial fibrosis spatial distribution and temporal onset may play a prognostic role, being involved in systolic and diastolic dysfunction, as well as arrythmias [ 37 , 38 , 39 , 40 , 41 , 42 ]. In HF patients, the myocardial fibrosis may vary in term of spread and entity, defining a personalized and specific fibrosis distribution pattern.…”
Section: The Pathophysiology Of Heart Failure With Preserved Ejection Fractionmentioning
confidence: 99%